The Role of Personality Profiles in the Longitudinal Relationship Between Work‐related Well‐being and Life Satisfaction Among Working Adults in Switzerland. Issue 1 (26th December 2019) - Udayar, Shagini; Urbanaviciute, Ieva; Massoudi, Koorosh; Rossier, Jérôme
Abstract: Drawing on the concept of spillover between work and life domains and using a person‐centred approach, the present study examined the role of Big Five personality trait profiles in moderating the relationship between work‐related well‐being and life satisfaction over a 1‐year period in a sample of working adults in Switzerland ( N  = 1204). Latent profile analysis was first carried out to derive and compare alternative latent personality profile models. Subsequently, a two‐wave cross‐lagged structural equation model using three personality profiles (resilient, average, and oversensitive) as moderators was tested. Work stress and job satisfaction were used as negative and positive indicators of work‐related well‐being. The results showed that in the overall sample, only Time 1 life satisfaction predicted Time 2 job satisfaction. We found a moderating role for the personality profiles, where the effect of Time 1 work stress on Time 2 life satisfaction became salient in the oversensitive profile, while a significant effect of Time 1 life satisfaction on Time 2 work stress was found in the resilient profile. The current study showed that different combinations of personality traits may determine the way in which work‐related well‐being and general well‐being relate to each other. © 2019 European Association of Personality Psychology